Poor Agreement Between Imaging and Histologic and Colonoscopy Findings in Pediatric Patients. Issue 2 (February 2018) - Chapa-Rodriguez, Adrian; Bhatia, Tavleen; Buckley, Andrew; Baker, Susan S.; Baker, Robert D.; Alkhouri, Razan H.
ABSTRACT: Background: Computed tomography scans (CTs), more recently magnetic resonance imaging, are often used to assess the gastrointestinal tract in patients complaining of abdominal pain. We aim to determine the strength of agreement among abdominal imaging, endoscopic, and histologic findings. Methods: Retrospective chart review of pediatric patients who underwent colonoscopy between January 1, 2012, and December 31, 2014, at Women and Children's Hospital of Buffalo. Patients who had abdominal and pelvic CTs or magnetic resonance imaging within 30 days before or after a colonoscopy were included. Results: One hundred two patients were included: mean age 12.7 ± 3.8 years, 66% girls. A total of 109 imaging studies were performed. Overall 61% of imaging studies were abnormal. The most frequent intestinal radiological findings were colonic wall thickening (CWT) (55%) and colonic wall enhancement (CWH) (24%). Free fluid (20%) and fat stranding (18%) were the most common extra-intestinal findings. Imaging studies agreed with histology in 81% and with colonoscopy in 75% with a moderate strength of agreement (k: 0.59 and 0.466, respectively). CWT agreed with histology in 74% with a moderate strength of agreement (k: 0.47). History of weight loss (OR 5.35, P  = 0.041), chronic diarrhea (OR 4.22, P  = 0.014), a positive lactoferrin (OR 7.00, P  = 0.011), and presence of CWT on imaging study (OR 5.20, P  = 0.001) were predictive of having abnormal histology. Conclusions: The strength of agreement among imaging, endoscopic, and histologic findings was suboptimal. Colonoscopy and imaging are both likely to be necessary in patients with suspected inflammatory bowel disease. Although colonoscopy may be superior in diagnosis of colitis, imaging may provide more information regarding small bowel disease.